The Influence of Leadership on Civil Servants’ Performance through Work Motivation and Job Satisfaction at the Department of Tourism and Culture of Teluk Wondama Regency - Manupapami, George; Taliang, Askar; Darmayanti, Tri; Saragih, Yansen M.I. (DINASTI RESEARCH, 2025)
The performance of Civil Servants (ASN) plays a vital role in achieving good governance, including within the Department of Tourism and Culture of Teluk Wondama Regency. However, ASN performance is often influenced by leadership, work motivation, and job satisfaction. This study aims to analyze the effect of leadership on work motivation, job satisfaction, and employee performance, as well as to examine the mediating roles of work motivation and job satisfaction. This research employed a quantitative approach with a causal cross-sectional design. The population consisted of 43 civil servants, with a final sample of 42 respondents selected using the census method. Data were collected using a questionnaire tested for validity and reliability, and analyzed through simple regression, multiple regression, and path analysis. The results show that leadership has a positive and significant effect on job satisfaction and performance, but no significant effect on work motivation. Work motivation positively and significantly affects employee performance, while job satisfaction has a negative but significant effect on performance. Path analysis indicates that both work motivation and job satisfaction mediate the relationship between leadership and performance, with job satisfaction acting as a negative mediator. In conclusion, leadership plays a crucial role in improving civil servants’ performance both directly and through the mediation of work motivation and job satisfaction. It is recommended that leaders adopt participative leadership styles, strengthen motivation through incentives and training, and manage job satisfaction so that it aligns with productivity improvement.